Data center fundamentals - Arregoces, Mauricio; Portolani, Maurizio; Safari eBooks (Indianapolis, Ind. : Cisco Press, 2004)
"Data Center Fundamentals helps you understand the basic concepts behind the design and scaling of server farms using data center and content switching technologies. It addresses the principles and concepts needed to take on the most common challenges encountered during planning, implementing, and managing Internet and intranet IP-based server farms. An in-depth analysis of the data center technology with real-life scenarios make Data Center Fundamentals an ideal reference for understanding, planning, and designing Web hosting and e-commerce environments"--Resource description page.
Description based on print version record.
Includes index.
Keywords: Data warehousing; Data libraries; Electronic books